Triglyceride-rich lipoproteins and cardiovascular diseases - Xu, Dandan; Xie, Lin; Cheng, Cheng; Xue, Fei; Sun, Chaonan (Frontiers in Endocrinology, 2024)
The global prevalence of cardiovascular diseases (CVD) continues to rise steadily, making it a leading cause of mortality worldwide. Atherosclerosis (AS) serves as a primary driver of these conditions, commencing silently at an early age and culminating in adverse cardiovascular events that severely impact patients' quality of life or lead to fatality. Dyslipidemia, particularly elevated levels of low-density lipoprotein cholesterol (LDL-C), plays a pivotal role in AS pathogenesis as an independent risk factor. Research indicates that abnormal LDL-C accumulation within arterial walls acts as a crucial trigger for atherosclerotic plaque formation. As the disease progresses, plaque accumulation may rupture or dislodge, resulting in thrombus formation and complete blood supply obstruction, ultimately causing myocardial infarction, cerebral infarction, and other common adverse cardiovascular events. Despite adequate pharmacologic therapy targeting LDL-C reduction, patients with cardiometabolic abnormalities remain at high risk for disease recurrence, highlighting the importance of addressing lipid risk factors beyond LDL-C.Recent attention has focused on the causal relationship between triglycerides, triglyceride-rich lipoproteins (TRLs), and their remnants in AS risk. Genetic, epidemiologic, and clinical studies suggest a causal relationship between TRLs and their remnants and the increased risk of AS, and this dyslipidemia may be an independent risk factor for adverse cardiovascular events.Particularly in patients with obesity, metabolic syndrome, diabetes, and 3 chronic kidney disease, disordered TRLs and its remnants levels significantly increase the risk of atherosclerosis and cardiovascular disease development.Accumulation of over-synthesized TRLs in plasma, impaired function of enzymes involved in TRLs lipolysis, and impaired hepatic clearance of cholesterol-rich TRLs remnants can lead to arterial deposition of TRLs and its remnants, promoting foam cell formation and arterial wall inflammation.Therefore, understanding the pathogenesis of TRLs-induced AS and targeting it therapeutically could slow or impede AS progression, thereby reducing cardiovascular disease morbidity and mortality, particularly coronary atherosclerotic heart disease.